87Sr/86Sr isotope ratios in trees as an archaeological tracer: Limitations of linking plant-biomass and bedrock Sr isotope signatures. (September 2021) - Erban Kochergina, Yulia V.; Novak, Martin; Erban, Vojtech; Stepanova, Marketa
Abstract: Assuming that strontium (Sr) isotope ratios in trees mirror the bedrock isotope signal, between-site 87 Sr/ 86 Sr comparisons can serve as a powerful tool in archaeological wood provenance studies. Here we discuss the strengths and weaknesses of this approach using Sr isotope data for bedrock, trees and rainfall collected at seven sites in the Czech Republic. The study included basalt, durbachite, granite, paragneiss, limestone and phyllitic slate. The range of 87 Sr/ 86 Sr ratios of these bedrock types was extremely large (0.704–1.743). The investigated tree species included oak, pine, and spruce. Within-tree variability in 87 Sr/ 86 Sr ratios ( 0.010) was two orders of magnitude smaller than the variability in Sr ratios across the studied bedrock types. Oak and pine growing on identical bedrock exhibited statistically indistinguishable 87 Sr/ 86 Sr ratios. In four types of spruce tissues from a particular site, the 87 Sr/ 86 Sr ratios were indistinguishable, while significantly different from spruce tissues at another site. The 87 Sr/ 86 Sr ratios of the wood differed from those of bedrock, converging to the 87 Sr/ 86 Sr ratio of rainfall (0.709–0.714). Even at a 450-km distance from the nearest sea, atmospheric Sr partly originated from sea-spray. Incorporation of atmospheric Sr in trees often results in overlapping 87 Sr/ 86 Sr ranges and hampers source identification of archaeological wood. Highlights: Comparing an artefact's 87 Sr/ 86 Sr with bedrock is insufficient to determine origin. Wood always contains a sizeable site-specific proportion of local atmospheric Sr. Method resolving power improves with increasing 87 Sr/ 86 Sr contrast to precipitation. Rather than confirming probable source areas, the method rules out inappropriate ones. Rb-rich minerals (rather than bulk rock Sr) determine 87 Sr/ 86 Sr in trees.